Quality of life of diabetes amputees following major and minor lower limb amputations - Mohd Yusof, Nazri; Che Ahmad, Aminudin; Sulong, Ahmad Fadzli; Mohd Adnan, Mohd Jazlan; Ab Rahman, Jamalludin; Musa, Ramli (Malaysian Medical Association, 2019)
Introduction: Minor amputation was performed as a salvage procedure because most of the patients were not able to ambulate and become dependent following major amputation. Minor amputation is defined as amputation at the level of ankle joint and below while major amputation is defines by amputation above the ankle joint. The aim of this study was to compare the quality of life among diabetes patients following major and minor amputations. Methods: A total of 94 diabetes patients were reviewed six months following amputation. Their walking ability, dependency status and quality of life were evaluated, using the Malay translated version of the Short Form Health Survey 36 (SF-36) questionnaire. Results: During the follow up only three patients (8.3%) following major amputation were dependant compared to 30 patients (51.7%) following minor amputation. Forty-nine (84.5%) of minor amputation and only 15 (41.7%) of major amputation patients were ambulating independently. Patients with minor amputation have significantly better Physical functioning, Role - physical, General health, Role – emotional, and Mental health score (p<0.001). However, they have worse BP and SF score than those following major amputation (p<0.001). The VT score of both groups were not significantly different. Conclusion: Patients with minor amputation are more independent, ambulatory and had better quality of life than those with major amputation. Despite the risk of persistent infection and amputation stump complication, minor amputation should be attempted in diabetes patients.